Indolicidin derivatives as potent dual-action antifungal and antibacterial agents for the treatment of skin infections: A comprehensive study from in vitro to in vivo evaluation - Hoa Ngo Van; Huy Luong Xuan; Hai Le Viet; Hai Bui Thi Phuong; Yen Do Hai; Nguyen Quoc Thang; Tung Truong Thanh; Thinh Vo Yen; Triet Nguyen Minh; Linh Nguyen Van; Hang Ngo Thu; Mao Can Van (PLoS ONE, 2025)
As listed by the WHO, the emergence of antibiotic-resistant pathogens, particularly Staphylococcus aureus and Pseudomonas aeruginosa, highlights the urgent need for novel antimicrobial agents. In parallel, fungal infections, especially those caused by Candida albicans, have also become increasingly prevalent and clinically challenging, further emphasizing the necessity for broad-spectrum therapeutic strategies. In particular, skin and soft tissue infections (SSTIs) caused by these bacteria and fungal are common in humans and can lead to severe complications if left untreated. Antimicrobial peptides (AMPs) have gained significant attention due to their broad-spectrum antimicrobial activity and immunomodulatory effects. Indolicidin, a naturally occurring cationic AMP, has demonstrated potent antibacterial and antifungal properties. In this study, we designed and synthesized a novel Indolicidin-derivative peptide IND-4,11K to enhance their antimicrobial activity and stability. The peptide was evaluated in vitro for their antimicrobial efficacy against Gram-positive, Gram-negative bacteria and Candida albicans. IND-4,11K was then prepared in 0–2% cream formula for in vivo testing in rabbit models. These findings suggest that modified Indolicidin-derivatives have potential as novel dual-action antimicrobial agents for treating resistant skin infections and warrant further preclinical investigations.